GENETIC VARIATION OBSERVED IN COMPOSITE SEEDLING SEED ORCHARD OF Acacia mangium Willd. AT CENTRAL JAVA, INDONESIA : IMPLICATIONS FOR INCREASING GENETIC GAIN AND SEED PRODUCTION - Arif Nirsatmanto (Indonesian Journal of Forestry Research, 2012)
As part of multiple-population breeding scheme using sub-lining system, a composite seedling seed orchard of was established at Central Java, Indonesia. The orchard comprises a combination of the best 40 plus tree families selected from four sub-lines in the first-generation of Acacia mangium progeny trial. The design of orchard is randomized complete block laid-out as four line tree-plot of six replications with a spacing of 2 x 4 meter. Variation among sub-lines and families within sub-line, andgenetic parameters for height, dbh and volume were investigated at age of 24 months. The aim of this study was to investigate genetic variation for growth traits in a composite seedling seed orchard and todiscuss the implication for increasing genetic gain and seed production. In general, trees derived from two sub-lines of Papua New Guinea (PNG) provenance showed better growth than those from Far North Queensland, Australia (FNQ). Analysis of variance revealed significant differences among sublines and families within sub-line for height, dbh and volume. Variation of the traits among families within sub-line accounted for 1.1% to 5.0%, and trees within family 43.8% to 65.8%. Heritability varied from 0.044 to 0.201 for individual, 0.060 to 0.229 for within-family and 0.098 to 0.383 for family. Withinfamily selection promoted high genetic gain for all traits, ranging from 1.3% to 4.4%. In order to increase genetic gain and seed productivity, it is recommended that:(1) the best plus trees included in the orchard should be selected based on their progeny test, (2) the design of plot size should be single treeplot, (3) the final density of seed trees should be twice greater than the number of trees intended forseed collection, which is about 300 trees per hectare.